Penggunaan Mekubar (Pop Up) untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Sekolah Dasar - Susanto, Joko (Jurnal Didaktika Pendidikan Dasar, 2019)
The completeness of activities and learning outcomes have not reached 75%, because the learning processes were implemented through image media both in the student’s book and discussion methods. The research problem is focused on how to increase the students’ learning activities and outcomes after learning with the mekubar (Pop Up). The research objective is to describe the increase in activity and learning outcomes of data processing material after being given learning with the mecubar (Pop Up). The design is a classroom action research. The subjects included children in grade VI SDN Rejosari 03 Semarang. The instrument consisted of observation, questionnaire, and learning outcomes sheets. The data analysis technique is conducted descriptively. The results show that the students’ activity increased from 73% to 87% and the learning outcomes from 77% to 91%. Learning mathematics through mekubar (Pop Up) has been interesting. Teachers can use learning media suitable for learning materials.